Impfungen in der Dermatologie - Sticherling, Michael (Hautarzt, 2021)
Vaccinations are among the most successful prophylactic measures in medicine. As they are applied to healthy subjects, regulatory steps before licensing of any vaccination are strictly based on clinically controlled studies as well as on registry data in the further course. The probability and relevance of adverse reactions to vaccinations have to be weighed against any harm through the respective natural infection as well as the vaccination-induced protection against infections. Intolerance reactions to vaccinations are far more suspected than proven and altogether rare. Among these, specific dermatoses like psoriasis, atopic dermatitis and lichen planus are found as well as allergic reactions and a number of more nonspecific skin symptoms. Apart from provocation or exacerbation of an underlying dermatological disease, various intolerance reactions may be encountered which are classically allergologic or anaphylactoid. People with chronic dermatoses, especially those on immunosuppressive and immunomodulatory therapy, should have all recommended standard vaccinations. Vaccinations should not be administered during acute skin manifestations and relevant comedication—especially if immunomodulatory or immunosuppressive—has be taken into account in the decision to vaccinate and to define the time point of any vaccination. Inactivated vaccines may be administered even during ongoing immunosuppressive therapy, but may result in decreased immunological reactions and protection to infection. Live vaccines should be avoided.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Adverse reactions; Atopic dermatitis; Intolerance reactions; Lichen planus; Psoriasis